2004
DOI: 10.3354/meps273121
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrially derived sediment: response of marine macrobenthic communities to thin terrigenous deposits

Abstract: Coastal marine habitats adjacent to catchments with encroaching human development are likely to experience increased sediment loadings in ensuing decades. Thus, sedimentary disturbance regimes in which coastal marine benthic communities have evolved may be shifting as depositional events exceeding critical thresholds become more frequent. To understand the threat posed by terrigenous sedimentation in an embayment with increasing urban development, we determined the thickness and frequency at which terrigenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 51 publications
7
57
0
Order By: Relevance
“…Blackburn and Henriksen, 1983;Glud, 2008;Hohaia et al, 2013;Huettel et al, 2003), as well as macrofauna behaviour and ecosystem functioning (e.g. Lohrer et al, 2004;Pratt et al, 2013;Woodin et al, 2012). Benthic macrofauna are known to influence nitrogen cycling (Aller, 1988;Kristensen et al, 1991;Laverock et al, 2011), and the presence of macrophytes and microphytobenthos is also expected to influence pore water nutrient concentrations and the level of experimental enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…Blackburn and Henriksen, 1983;Glud, 2008;Hohaia et al, 2013;Huettel et al, 2003), as well as macrofauna behaviour and ecosystem functioning (e.g. Lohrer et al, 2004;Pratt et al, 2013;Woodin et al, 2012). Benthic macrofauna are known to influence nitrogen cycling (Aller, 1988;Kristensen et al, 1991;Laverock et al, 2011), and the presence of macrophytes and microphytobenthos is also expected to influence pore water nutrient concentrations and the level of experimental enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental deterioration produced by glacial activity in fjordic basins did not result in reduction of the rare species component of the total richness. This was an unexpected pattern as, for example, Lohrer et al (2004) showed in experiments that deposition of terrigenous sediment on marine benthic assemblages resulted in species impoverishment, and rare species were eliminated first. Benedetti-Cecchi et al (2008) documented a strong vulnerability of rare species to environmental variability and disturbances, and systems impacted by human disturbance often exhibit reductions in both diversity and numbers of rare species (e.g.…”
Section: Species Rarity In Fjords and Open Shelf Systemsmentioning
confidence: 99%
“…Bioturbation and bio-irrigation can be significantly altered under increased sediment deposition through changes in macrobenthic densities (Alves et al, 2017) or behaviour (Rodil et al, 2011). For example, sessile organisms that live attached to the substratum or in tubes often have a limited capacity to escape burial, and suspension feeders risk clogging of their feeding apparatus (Ellis et al, 2002;Lohrer et al, 2004). Secondly, macrofauna activities can interfere with the deposition induced physical barrier at the sedimentwater interface.…”
Section: Introductionmentioning
confidence: 99%